Serum miR‐19a expression correlates with worse prognosis of patients with non‐small cell lung cancer. Issue 7 (23rd April 2013) - Lin, Qunying; Chen, Tingjian; Lin, Qingyu; Lin, Guosheng; Lin, Juan; Chen, Guohuan; Guo, Lijing
Abstract Objectives The aim of this study was to investigate the expression levels of miR‐19a in non‐small cell lung cancer (NSCLC) tissue and serum, and to clarify the relationships of serum miR‐19a expression with clinical factors and prognosis of NSCLC patients. Methods Expression levels of miR‐19a in 25 paired NSCLC, paracancerous tissues and serum, and sera from 103 controls and 201 NSCLC patients were respectively detected using real‐time quantitative PCR. Results Compared with the paracancerous tissue, miR‐19a was overexpressed in NSCLC tissue (P = 0.006), and there was a strong correlation between expression levels of miR‐19 in 25 paired sera and tissues (P = 0.001). Serum miR‐19a expression in NSCLC patients was significantly upregulated compared with those in healthy individuals (P = 0.001). High serum miR‐19a expression was significantly correlated with TNM stage and lymph node metastasis (P = 0.004 and 0.017, respectively). Survival analysis revealed that overall survival rate of patients with high serum miR‐19a expression was significantly worse than those of patients with low serum miR‐19a expression (hazard ratio = 1.438, 95% confidence interval 1.007–2.052, P = 0.046). Conclusion High serum miR‐19a expression may be an independent poor prognostic factor for survival in NSCLC patients. J. Surg. Oncol. 2013;107:767–771. © 2013 Wiley Periodicals, Inc.